2014
DOI: 10.1002/hyp.10175
|View full text |Cite
|
Sign up to set email alerts
|

The source and fate of sediment and mercury in Hunza River basin, Northern Areas, Pakistan

Abstract: This article presents results of mercury in surface waters from Hunza River basin, Northern Areas, Pakistan. Small‐scale gold mining activities along the Hunza and Gilgit rivers are long known to be discharging mercury in the amalgamation and roasting processes. Previous studies reported high mercury concentrations in soils close to mining operations as well as serious health problems for miners. However, none of the studies have focused on the level of contamination in aqueous environments. This is the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Given the correlation between total suspended solids (TSSs) and water column total Hg concentration found in this study (P < 0.0001, r 2 = 0.62; fig. S3) and other studies (23)(24)(25), as well as the higher concentration of TSS in downstream rivers compared with the other measured water bodies (P < 0.0001; fig. S4), we expect that Hg is transported bound to sediment particles (i.e., as particulate Hg) rather than in the dissolved fraction.…”
Section: Landscape Patterns In Mercury Concentrationmentioning
confidence: 49%
“…Given the correlation between total suspended solids (TSSs) and water column total Hg concentration found in this study (P < 0.0001, r 2 = 0.62; fig. S3) and other studies (23)(24)(25), as well as the higher concentration of TSS in downstream rivers compared with the other measured water bodies (P < 0.0001; fig. S4), we expect that Hg is transported bound to sediment particles (i.e., as particulate Hg) rather than in the dissolved fraction.…”
Section: Landscape Patterns In Mercury Concentrationmentioning
confidence: 49%
“…However, there is a great need to explore the economic potential of the region through advanced level geophysical, geochemical and spectroscopic and remote sensing techniques. The occurrence of gold particles in the Indus river and its tributaries flowing through this region (Tahirkheli 1974;Austromineral 1976Austromineral , 1978Halfpenny and Mazzucchelli 1999;Shah and Khan 2004;Ali et al 2014;Biber et al 2014) and the hydrothermally altered sulfide-bearing zones reported in various parts of the region (Sheikh et al 2014;Miandad et al 2014;Rehman et al 2015) suggest that there could be the possibility of occurrence of source rocks for precious and base metals mineralization in the region. But due to the remoteness and inaccessibility to rugged terrains in this part of the Himalayan region, we need to adopt such techniques which can scan the whole region for the differentiation of various lithological units and hydrothermally altered mineralized and un-mineralized zones.…”
Section: Introductionmentioning
confidence: 91%
“…It can cause miscarriages in pregnant women, severely damage the brain and kidneys of developing fetuses and, ultimately, causing death [ 26 , 27 , 28 ]. Mercury is regarded as more toxic than other non-essential metals [ 29 , 30 ] and can cause cancer [ 31 , 32 ] and a variety of other disorders affecting the immune system, heart, kidneys, lung and liver [ 29 , 33 , 34 , 35 , 36 , 37 , 38 ]. Essential elements at high levels can also have toxic effects [ 39 ].…”
Section: Introductionmentioning
confidence: 99%